Review of gas adsorption in shales for enhanced methane recovery and CO 2 storage - Rani, S. (2019)
The concept of increased methane recovery with simultaneous CO 2 sequestration in unconventional reservoirs like gas shales has been studied extensively. A clear understanding of storage mechanism and geo-chemical characteristics of shale gas reservoirs is necessary for predicting the gas reserve and evaluating reservoir potential. The present article reviews literature on adsorption of methane and carbon dioxide on shale for the purpose of methane recovery with simultaneous CO 2 sequestration in shale gas reservoirs. The objective of this article is to discuss the technical aspects related to gas adsorption and characterization (both composition and pore) concerning shale gas reservoirs. The various adsorption mechanisms, different adsorption isotherm types and shales as a microporous adsorbent are discussed. Using the published information in literature, methane and carbon dioxide adsorption in shales and its relationship with different geochemical parameters like organic matter content, mineralogy, pore-structure and moisture as essential controls for gas adsorption in shale are discussed. Studies that answer the concerns on effect of shale composition and pore characteristics on adsorption capacity of heterogeneous shale are also summarised. Â© 2018